RAÇA, GÊNERO E EDUCAÇÃO EM “ÚRSULA” E “CANTOS À BEIRA-MAR” DE MARIA FIRMINA DOS REIS - BARBOSA, Tatiara (2022)
This dissertation addresses the question of the continuity of colonial forms of exploitation experienced by black women, in a society crossed by racial and gender relations, where Literature presents itself as an important resource to problematize such reality, in the opposite direction of the patterns of domination and dissemination of knowledge. Thus, the question that mobilizes this study is to understand how the afro-feminine theme and the educational phenomenon are manifested in the thought produced by Maria Firmina dos Reis in the works “Úrsula and Songs at Sea Shore”. Our general objective is to analyze the afro-feminine theme and the educational phenomenon in the thought produced by Maria Firmina dos Reis in her works “Úrsula and Songs at Sea Shore” and their resonances in social relations. Therefore, it was necessary to characterize the historical context of the thought produced by the author in her works; to identify in the novel and in poems the relations among race, gender and education and possible contributions to Literature teaching. As a technical product resulting from this study, we created an e-book with the story of Maria Firmina dos Reis, either in text and in comics, in order to insert and discuss her life in basic education schools. With regard to the methodology, this is a bibliographical study, whose approach is qualitative, centered on the literary works “Úrsula and Songs at Sea Shore”, focusing on the issues of race, gender and education and their interrelationships. Results show that the author has already presented herself as a woman ahead of her time, who was not intimidated by the issues imposed by the white man on society, and who has made a great contribution to the literary canon, being an important precursor of Afro-female Brazilian writing.